Operating SMEs in the Face of the Covid-19 Pandemic in Calabar - Mary U. Ojong-Ejoh; Pius U. Angioha; Rose U. Agba; Evaristus A. Aniah; Maruf Gbadebo Salimon; Abayomi Akintola (Yayasan Ahmar Cendekia Indonesia, 2021)
This study examines the impact of the covid-19 pandemic on small and medium scale enterprise Operation in Calabar, Cross River State, Nigeria. The cross-sectional survey method was used in collecting data from 474 SMEs in Calabar, Cross River State using the stratified and purposive sampling technique. The instrument of data collection was a self-developed semi-structured questionnaire. Data collected from the field was coded, analyzed using descriptive statistics such as tables and graphs and correlation analysis at 0.05 level of significance. Out of the 474-instrument distributed only 422 was returned and used for analysis. From the analysis, the result revealed that 88.6 per cent of the SMEs reported being negatively affected by the pandemic, 71.3 per cent reported laying off employees during this period. Also result from the correlation analysis revealed that there is a significant relationship between covid-19 pandemic and the operations of SMEs in Calabar, Cross River State, Nigeria. Based on these findings, there is a need for policy adjustment toward SMEs operations in Calabar